Simulation Analysis of an Ankle Prosthesis Design Using Shock Absorbers to Support Prayer Movements - Winarno, Agil; Suyitno, Suyitno; Mahendra, Raka (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2026)
Amputation of the lower limb causes limitations in performing daily activities, including praying (salat), which requires dynamic movements such as standing, bowing, prostrating, and sitting. This study aims to design and manufacture an ankle-foot prosthesis prototype that allows users to perform salat movements normally without removing the prosthesis. The design process was carried out using Computer-Aided Design (CAD) software to create a 3D model and analyze structural strength through Finite Element Analysis (FEA). The prosthesis was made from aluminum A356 material and fabricated using metal casting and machining methods. The simulation results showed that the maximum stress occurred at the upper front part of the ankle, with a value of 15.14 MPa, which is still below the material’s strength limit, indicating that the design is safe. The prototype produced was consistent with the design and capable of supporting dorsiflexion up to 20° and plantarflexion up to 50°, with a shock absorber mechanism that operates smoothly without jerks. Therefore, the designed ankle-foot prosthesis can provide comfort and flexibility for people with disabilities when performing salat.